P013 When is a hernia not a hernia and lymphoma not lymphoma?. (30th June 2016) - Hamill, Matthew
Abstract : Background/introduction: Lymphogranuloma vereneum (LGV) is a relatively common cause of proctitis and other gastrointestinal symptoms in men who have sex with men (MSM). Other symptoms and signs may present and unless a careful sexual history is taken STI may not be considered in the differential diagnosis. Aim(s)/objectives: To illustrate the potential for mis/inaccurate diagnosis of groin swellings in sexually active MSM and provide a case that can be used for teaching primary care, surgical, oncology and histopathology colleagues. Methods: We present a case of a 55 year old HIV-infected MSM who presented to surgical colleagues with left groin swelling. Results: The patient underwent open surgery to repair an inguinal hernia. At surgery he was found to have significant inguinal lymphadenopathy. Histopathological analysis at the regional pathology centre identified a B cell lymphoma and referral was made to a haematologist to start anti-cancer therapy. In the interim the patient attended our GUM service, was diagnosed with rectal LGV and treated with antibiotics. His lymphadenopathy resolved and staging CT was negative. Discussion/conclusion: Careful consideration of the differential diagnosis of inguinal swelling should be undertaken and STI excluded prior to general anaesthesia and operative procedures whenever possible. Had this patient not attended his GUM clinic he may have undergone potentially toxic chemotherapy to treat LGV infection. This case serves to illustrate the need for open communication between GUM and other medical colleagues.